Balancing Workers' Protection and Labor Market Flexibility in China - World Bank (World Bank, Washington, DC, 2021)
Across the world, governments use minimum wages, employment protection legislation, and other labor regulations that define the legal boundaries of employment to manage potential labor market imperfections. These imperfections include information asymmetry, uneven market power between employers and employees, discrimination by employers, and incomplete markets for unemployment insurance and insurance for other work-related risks. Labor regulations are also widely used to further other objectives, most notably the distribution of wealth among the population. Labor regulations can have a wide range of impacts on the employment and earnings of workers and the productivity and profits of firms. While these regulations have become common currency in most countries, many economists believe that over-regulation of labor markets can have detrimental consequences. In fact, until relatively recently, most economists were skeptical that labor regulations could have any positive impacts on either workers or firms. In recent years, a more nuanced view has emerged that argues that both over-regulation and under-regulation can constrain job creation and have other negative impacts, including exacerbating inequalities in the labor market. The proponents of this view assert that over-regulation can reduce labor market flexibility, while under-regulation can leave workers unprotected by not correcting for labor market imperfections. In practice, striking the right balance between workers’ protection and market flexibility is not easy. From a political economy point of view, different groups with special interests lobby vigorously either for further protection or further flexibility. As a result, minimum wages and employment protection legislation are often highly politicized issues. However, even from a technical point of view, it is not easy to draw unequivocal conclusions about the impact of labor regulations on employment levels, earnings, job turnover, productivity, and other outcomes because of the ambiguity of theoretical models and the scarcity of empirical evidence on the causal impacts of labor regulations. Empirical evidence is even scarcer for developing and emerging economies than for developed countries.